Dominican Republic : Leveraging Competition in the Telecom Sector to Accelerate Economic Growth - World Bank (World Bank, Washington, DC, 2021)
Limited competition hinders the optimal use of telecommunication services in the Dominican Republic, which lags peer countries in mobile subscriptions and internet penetration. Despite recent reforms designed to enhance competition, the telecommunications sector remains dominated by a small number of companies. In addition, the antimonopoly policy is perceived to be weak compared to regional peers. High infrastructure costs limit the economic viability of replicating key facilities, creating bottlenecks. Fixed telecom prices have remained largely unresponsive to changes in demand over the last eight years. Moreover, prices for both mobile communications and fixed broadband are higher in the DR than in peer countries. Following the World Bank Group’s Markets and Competition Policy Assessment Toolkit (MCPAT), this policy note provides a brief overview of key bottlenecks affecting the telecommunications sector, as well as key pro-competition reforms that could improve the regulatory landscape. Due to its inherent characteristics, the telecommunications markets, fixed, mobile and internet, in DR are concentrated. Currently, there are three main operators in the fixed, mobile and internet markets, with few smaller operators having a residual market share in the fixed and internet markets. While market concentration is common in the telecommunication sector in many countries, the interaction between market characteristics and the regulatory framework for telecommunications is key to yield efficient market outcomes in terms of prices, quality and access to services.